2013
DOI: 10.2337/dc11-2546
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome Model Definitions Predicting Type 2 Diabetes and Cardiovascular Disease

Abstract: OBJECTIVEMetabolic syndrome (MetS) is a cluster of abdominal obesity, hyperglycemia, hypertension, and dyslipidemia, which increases the risk for type 2 diabetes and cardiovascular diseases (CVDs). Some argue that MetS is not a single disorder because the traditional MetS features do not represent one entity, and they would like to exclude features from MetS. Others would like to add additional features in order to increase predictive ability of MetS. The aim of this study was to identify a MetS model that opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 30 publications
1
37
0
4
Order By: Relevance
“…In the present study, we evaluated the association of MetS as a whole as well as the individual risk components with the different parameters of cognition. Povel et al [37] had suggested that using the NCEP ATPIII definition to compose one entity from MetS risk factors, MetS could predict Type 2 Diabetes and cardiovascular disease. However, it may not necessarily be applicable to cognition assessment.…”
Section: Age Groupsmentioning
confidence: 99%
“…In the present study, we evaluated the association of MetS as a whole as well as the individual risk components with the different parameters of cognition. Povel et al [37] had suggested that using the NCEP ATPIII definition to compose one entity from MetS risk factors, MetS could predict Type 2 Diabetes and cardiovascular disease. However, it may not necessarily be applicable to cognition assessment.…”
Section: Age Groupsmentioning
confidence: 99%
“…Metabolic syndrome is a pathological condition in humans, characterized by dyslipidemia, altered glucose metabolism, insulin resistance, hypertension, an increased risk of type 2 diabetes and often obesity (Povel et al, 2013;Silva et al, 2014). In humans, as type 2 diabetes progresses, insulin secretion declines.…”
Section: Hormonal Regulation Of Metabolismmentioning
confidence: 99%
“…Studies from the United States and Europe have shown high prevalence rates of MetS among patients with T2DM, ranging from 70 to 89% [Beltrán-Sánchez, Harhay, Harhay & McElligott,2013;McGill, Molyneaux, Twigg &Yue,2008;Povel et al,2013].…”
Section: Introductionmentioning
confidence: 99%